Literature mapping: critical factors in industrialized building system plastic formwork application - Ghazali, Muhammad Azuan Anif; Bahardin, Nur Fadhilah; Zaidi, Mohd Azian; Baharuddin, Mohd Nurfaisal; Yusof, Mohd Reeza (2016)
Industrialized building system (IBS) in Malaysia has been practiced for decades.The development of its formal practice parallels with the improvement of the built environment in the nation.One of the applications is on formwork.IBS plastic formwork has been promoted by Construction Industry Development Board Malaysia as an alternative to replace the conventional formwork system but the involvement from the public and private sectors in applying the IBS plastic formwork is seen reluctant.The aim of this study is to review the gaps that exist especially on awareness and readiness in application of IBS plastic formwork. Very relying on literature, this paper discovered a gap that is considered as critical factors in the successful of IBS plastic formwork application in construction industry.This paper aims to give new bits of knowledge in IBS formwork to upgrade the application of IBS plastic formwork as well as an alternative solution to enhancing the used of IBS in Malaysia.